Self-management of type 2 diabetes using a co-designed text based mobile health (mHealth) intervention in Nepal: A study protocol for randomised controlled trial - Namuna Shrestha; Padam Simkhada; Om Kurmi; Shiva Gautam; Biraj Karmacharya; Akina Shrestha; Rajendra Tamrakar; Ak Narayan Poudel (PLoS ONE, 2025)
Mobile health (mHealth) is increasingly being used for managing chronic diseases proving its feasibility, acceptability and effectiveness in improving the health outcomes. However, effectiveness of mHealth intervention for self-management of Type 2 diabetes remains unexplored in the context of Nepal. This study aims to develop and evaluate the effectiveness of a co-designed text based mobile health intervention for self-management of Type 2 diabetes in Nepal. We will conduct a six month, two arm (1:1) parallel group randomised control trial involving 154 adults with Type 2 diabetes. The primary outcome includes change in haemoglobin A1c level at six months follow up. Secondary outcomes include change in self-management outcomes such as self-efficacy, perceived support, diabetes related stress, health related quality of life and self-care activities. Primary and secondary outcomes will be summarized descriptively, and comparisons will be made using chi-square tests for categorical data and independent sample t-tests for continuous data. The trial is registered at ClinicalTrials.gov (NCT06623006).